2015
DOI: 10.1039/c5ra08971a
|View full text |Cite
|
Sign up to set email alerts
|

Controlled growth of in situ silica in a NR/CR blend by a solution sol–gel method and the studies of its composite properties

Abstract: Silica is grown in situ into a natural rubber (NR)/chloroprene rubber (CR) blend (at 40/60 ratio), by a solution sol-gel method, where the silica content in rubber blend is increased in a controlled manner exceeding the limit found for the same blend ratio in the soaking sol-gel method. Reaction conditions have been optimized to get adequate conversion of tetraethoxysilane (TEOS, a silica precursor) to silica. Rheological, thermal, mechanical and viscoelastic properties of all the composites are compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The glass transition temperature ( T g ) of the silica filled composites, as observed in the tan δ vs. temperature plot [Figure (c–d)], remains almost unaltered with respect to that of unfilled composite. Such findings are reported for reinforced CR and styrene‐butadiene‐rubber (SBR) where T g of the composites are found to remain unaffected by the presence of silane coupled silica particles. However, for the composite with γ‐APS integrated in situ silica, maximum reduction in tan δ peak height is observed.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The glass transition temperature ( T g ) of the silica filled composites, as observed in the tan δ vs. temperature plot [Figure (c–d)], remains almost unaltered with respect to that of unfilled composite. Such findings are reported for reinforced CR and styrene‐butadiene‐rubber (SBR) where T g of the composites are found to remain unaffected by the presence of silane coupled silica particles. However, for the composite with γ‐APS integrated in situ silica, maximum reduction in tan δ peak height is observed.…”
Section: Resultssupporting
confidence: 55%
“…Also, there are few reports on the improvement of properties of silica filled rubber like NR and EPDM by addition of a small amount of CR owing to strong CR–silica interaction that improves the silica dispersion and mechanical properties of the composites . In this context, role of sol–gel derived nanosilica, generated in situ in the CR matrix, in improving the silica dispersion and mechanical properties of the CR composites appears to be very promising …”
Section: Introductionmentioning
confidence: 99%
“…Studies on the rubber blends, filled with in situ silica, are rather scanty in literature. Of late, we have reported several interesting results on in situ silica generation in rubber blends comprised of nonpolar (NR) and polar (CR or NBR) rubber [22][23][24]. Our studies revealed that in situ silica could significantly enhance the compatibility of the heterogeneous immiscible rubber blend in addition to its appreciable reinforcement effect.…”
mentioning
confidence: 70%
“…These results are well supported by the increased crosslinking density values along the series which are derived from Flory-Rehner equation of vulcanized composites (Eq. 3; Table 3) that is generally followed in many reported work [15,23,24,35]. We have also determined equilibrium swelling ratio of the rubber phase Q r considering Krause equation, that is applicable for highly reinforcing filler system (Eq.…”
Section: Curing Characteristicsmentioning
confidence: 98%
“…Given this most scientific efforts are devoted to developing novel sustainable filler materials to enhance the mechanical strength of rubber products . These fillers are primarily classified into two categories (1) black fillers, for example, carbon black, carbon nanotubes and (2) nonblack fillers such as nanostructure silica, clay, and alumina . Although fillers tend to improve the mechanical properties of the rubber matrix, the filler reinforcement mechanism is still complicated and remains in debate.…”
Section: Introductionmentioning
confidence: 99%